FINANCIAL ASPECTS OF ESTABLISHING THE INSTITUTION OF THE SELF-EMPLOYMENT - V. V. Poliakova; S. L. Sumbatyan; V. A. Basalaev (Вестник университета, 2020)
The concept of self-employment as a form of individual entrepreneurship has been considered. A detailed analysis of the experience of foreign countries in establishing the institution of the self-employment,common and distinctive features of the applied models of the development of self-employment in European countries, Australia and the USA, has been presented. Much attention has been paid both the characteristic of the category “self-employed citizens” and the review of their areas of activity in Russia today. Available mechanisms and tools for the development of self-employment have been analyzed. Particular attention has been paid to the analysis of the concept of self-employment and its forms, presented in legislative acts, which serve as the basis for effective regulation by the government. Conclusions and recommendations of the authors on the application of the new special tax treatment on the income of self-employed citizens, implemented as part of a pilot project in several regions of the Russian Federation, have been presented.